Information security management handbook, vol. 6 - Tipton, Harold F.; Nozaki, Micki Krause (Boca Raton : Auerbach Publications, 2007)
Updated annually, this is a compilation of the fundamental knowledge, skills, techniques, and tools required by security professionals. This book sets the standard on which all IT security programs and certifications are based. It includes coverage of each domain of the Common Body of Knowledge, the standard of knowledge required by IT security professionals worldwide.
Includes bibliographical references and index.
oif 17/09/14
Loan
Keywords: Computer security; Data protection